Toward new biomarkers of cold tolerance: microRNAs regulating cold adaptation in fish are differentially expressed in cold-tolerant and cold-sensitive Nile tilapia (Oreochromis niloticus) - Blödorn, Eduardo B.; Martins, Amanda W.S.; Dellagostin, Eduardo N.; Nunes, Leandro S.; da Conceição, Rita C.S.; Pagano, Antônio D.; Gonçalves, Natiéli M.; dos Reis, Luana F.V.; Nascimento, Mariana C.; Quispe, Dionet K.B.; Fróes, Charles N.; Tavares, Rafael A.; et al. (Elsevier, 2024)
Overcoming the negative effects of cold stress in Nile tilapia (Oreochromis niloticus) is of great interest for the overall aquaculture economy. Recent evidence suggests that microRNAs may regulate mechanisms of cold adaptation in fish and could be potential biomarkers of cold tolerance in these animals. However, information on how microRNAs regulating cold adaptation in fish are expressed in cold-tolerant and cold-sensitive fish is still scarce. Therefore, the aim of the present study is to investigate the relationship between a panel of previously identified differentially expressed microRNAs in fish exposed to low temperatures and their association with cold tolerance in Nile tilapia. To this end, fish were individualized based on their weight and length, and subjected to a critical thermal minimum (CTmin) test. Blood samples were collected before and after the CTmin test. After the CTmin, brain and liver tissues were collected. Fish were separated into cold-tolerant and cold-sensitive based on their CTmin results. Untreated fish were used as control. The relative expression of miR-9-3p, miR-135c, miR-9-5p, miR-30b, miR-122, miR-92a was assessed through qPCR. Additionally, qPCR was used to measure the mRNA relative expression of IGF-I and SCD in the tissues. Cortisol and biochemical parameters were determined in plasma samples. As a result, miR-92a was up-regulated in the liver of cold-sensitive fish and in the blood of cold-tolerant fish post-CTmin. miR-30b was up-regulated in the blood and liver of cold stressed fish. In the brain, miR-9-5p and miR-9-3p were up-regulated in cold-tolerant fish post-CTmin. Furthermore, miR-122 and miR-135c expression levels remained similar to the control post-CTmin. In addition, miR-122 and miR-92a were differentially expressed in the blood of cold-tolerant and cold-sensitive Nile tilapia pre-CTmin. Therefore, besides regulating fish cold acclimation responses differently in cold-tolerant and cold-sensitive fish, miRNAs may also regulate pre-existing physiological conditions that are determinant to cold tolerance in Nile tilapia. In the transcriptional level, SCD expression increased in both cold-tolerant and cold-sensitive fish post-CTmin. Cold-tolerant Nile tilapia post-CTmin had increased levels of plasma cholesterol and IGF-I mRNA in the liver, which could mean an adaptive advantage. The present findings provide new insights on the role of post-transcriptional regulation of cold tolerance in Nile tilapia. Furthermore, miRNAs differentially expressed in cold-tolerant Nile tilapia may be potential targets for the development of new biomarkers and aid in the breeding of cold-tolerant strains in this species.
Keywords: Cold resistance; Cold stress; Epigenetic marker; Physiological plasticity